DEVELOPMENT OF ENGLISH SPEAKING BASED ON STORYTELLING TO OVERCOME THE DIFFICULTIES - Rizka Rahmadhani Siregar; Salamuddin Selian (Universitas Dharmawangsa, 2022)
ABSTRACT: This study aims to determine the development, validity and effectiveness of English speaking by storytelling to overcome the difficulties. This research is a research and development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The instruments used in this research are test, Lesson Plan assessment questionnaire (Very Bad, Not Good, Not So Good, Good, and Very Good), digital storytelling assessment questionnaire by media expert, and Student response questionnaire analyzed qualitatively based on their answers in the form of Agree and Disagree. Hasil uji dari validator melalui desain media secara keseluruhan mendapatkan kriteria sangat layak (88,33%) sehingga Bahan Ajar dapat digunakan sebagai bahan ajar peserta didik dalam proses pembelajaran. Material validation results are 93.3% and media validation results are 98.3%. Based on the two validity criteria that have been explained, the results of the material and media designed are Very Valid with descriptions that can be used without revision. The results of the effectiveness of the test are 75% of these results indicate that storytelling materials and media are effectively used in learning English, especially in speaking.Keyword: English Speaking, Development, Storytelling